Primary Hyperparathyroidism with Severe Hypercalcemia in Pregnancy Complicated by Acute Pancreatitis; A Rare Case Report And Literature Review - Alhabardi, Nadiah M. (مجلة الجزيرة للعلوم الصحية; مجلد 12 عدد 1 (2016), 2016)
Abstract: Background: Primary hyperparathyroidism with pancreatitis is very rare during pregnancy. The pregnant state presents a challenge to the diagnosis of hypercalcemia related to the many physiological changes that occur. Objective: To report a case of primary hyperparathyroidism in a pregnant patient, and to advocate a successful management with satisfactory outcome. Results: A 36-year-old multigravida Saudi woman presented during her 34th week of gestation with a five days history of epigastric pain, nausea and vomiting.Diagnosis was made as Primary hyperparathyroidism with severe hypercalcemia in pregnancy complicated by acute pancreatitis. She was initially managed with conservative medical measures and due to the failure of medical management, a multidisplinary team decided to terminate the pregnancy by cesarean section and to do parathyroidectomy at the same time at 34-weeks gestation. The maternal and fetal outcome was quite satisfactory. To the best of our knowledge, this is one of the rare case report in the literature with such finding and satisfactory outcome. Conclusions: Early diagnosis and appropriate management of Primary Hyperparathyrodisim (PHP) during pregnancy is important for better outcome. Multidisciplinary management decisions can significantly reduce the morbidity and mortality associated with the disease during pregnancy.